T. Rex trick-or-treats - Grambling, Lois G.; Davis, Jack E. (New York : Katherine Tegen Books, 2005)
Eager to do something special for Mother's Day, T. Rex decides to surprise his mother by decorating her car.
Ages 3-6.
Keywords: Dinosaurs -- Juvenile fiction